Optimization of the cylindrical sieves for separating threshed rice mixture using EDEM - Yuan, Jianbo; Wang, Jufei; Li, Hua; Qi, Xindan; Wang, Yongjian; Li, Chao (International Journal of Agricultural and Biological Engineering, 2022)
The design of the cylindrical sieve equipment used for the screening and separation of agricultural granular materials is mainly through the experimental method, which has the disadvantages of a long development cycle and high cost. To solve this problem, the discrete element method (DEM) was utilized to accurately build the particle models of threshed rice components (grains, shriveled grains, and short stalks), and simulated the separation of grains from the mixture in a cylindrical sieve. The influences of rotational speed (A), cylindrical sieve diameter (B), cylindrical sieve aperture (C), and inclinational angle (D) on screening cleaning rate, screening loss rate, and screening efficiency were investigated. Meanwhile, the optimal parameters of the cylindrical sieve were obtained using a central composite design (CCD) under response surface methodology (RSM). The results of CCD showed that the quadratic multinomial model is credible and revealed that the cylindrical sieve aperture has a significant impact on the screening characteristics. It is predicted that the optimal values for screening cleaning rate, loss rate, and efficiency were 97.84%, 0.27%, and 85.38%, respectively, while A, B, C, and D were 23.6 r/min, 297 mm, 8.7 mm, and 2°, respectively. The experimental results using a real threshed rice mixture were found to be in good agreement with the optimal simulation results. This study proved a reliable research method and provides a design reference for the cylinder sieving systems for threshed rice or separation of other bulk material. Keywords: cylindrical sieve, threshed rice mixture, discrete element method, separation, rice, optimization DOI: 10.25165/j.ijabe.20221502.5150 Citation: Yuan J B, Wang J F, Li H, Qi X D, Wang Y J, Li C. Optimization of the cylindrical sieves for separating threshed rice mixture using EDEM. Int J Agric & Biol Eng, 2022; 15(2): 236–247.